A Parallel Reporting System for Water Resources: From the Logic of Introduction of Natural Resource Balance Sheeting in China - Liu, Jiaqi; Wang, Zhan; Yin, Linsen; Liu, Ying (Frontiers in Environmental Science, 2022)
Water shortage has become a widespread problem worldwide. Preparation of water resource balance sheet forms the basis of regional environmental governance in China and is of great importance for achieving the sustainable development. This study is an attempt of developing a water resource accounting system on an accrual basis by preparing balance sheet and other essential supporting statements for Wuhan within the framework of a parallel reporting system, which is oriented to different objectives. The results show that during 2014-2020 the physical volume of Wuhan's water resources fluctuated with net precipitation to a large extent. Since 2017, the value of Wuhan's water has kept increasing even though the water volume of 2017-2019 still declined due to the earlier drought. This demonstrates a relatively better water management performance during the current terms of office, which indicates a positive role of the leadership accountability system based on natural resource balance sheeting that is being implemented in China. This study contributes to the literature on regional water resources accounting and environmental management. The water resource statements prepared for Wuhan, Hubei, China have a good level of generality. They provide a reliable basis for the local government's performance assessment of water resources management and facilitate the implementation of water resource related policies.